Математичне моделювання та обчислювальні методи дослідження ергатичних систем з динамічним захистом - Мохаммад Ракан Абед Алнабі Альджаафрех (My University, 2018)
Проблема підвищення безпеки людино-машинних (ергатичних) систем була та залишається надзвичайно актуальною. Її розв’язання здійснюється шляхом вбудовування в ергатичну систему спеціально розробленої підсистеми захисту та підвищення швидкодії динамічного захисту до гранично досяжних значень при обмеженнях на її вартість. У дисертаційній роботі запропоновано вирішення актуальної науково- практичної задачі підвищення безпеки ергатичних систем з динамічним захистом від шкідливих та небезпечних чинників. Метою дисертаційної роботи є підвищення безпеки ергатичних систем з динамічним захистом за рахунок розробки математичних моделей та удосконалення обчислювальних методів їх аналізу. Для досягнення поставленої мети вирішені завдання: виділення класу ергатичних систем з динамічним захистом від шкідливих та небезпечних чинників; розробки нелінійної моделі процесів взаємодії джерел шкідливих викидів з системою динамічного захисту; дослідження умови стійкості та адаптованості ергатичних систем з динамічним захистом; проведення структуризації загальної моделі на часткові сингулярні підмоделі з примежовим шаром, які дозволяють адекватно описувати динаміку різних типів ергатичних систем з суттєво різними швидкостями виділення шкідливих чинників та захисту від них в початкових стадіях розвитку катастроф; модифікації або розробки нового асимптотичного методу для дослідження динамічних властивостей ергатичних систем з динамічним захистом; розробки методу оцінювання та оптимізації вартості системи захисту в залежності від її технічних та динамічних властивостей. Методи дослідження дисертаційної роботи основані на комплексному використанні: системного аналізу для виявлення зв’язків, впливів та динамічних властивостей технічних систем з захистом; якісної теорії сингулярних диференційних рівнянь, що моделюють такі системи, для виділення стаціонарних множин та умов їх стійкості; асимптотичних методів для дослідження моделей ергатичних систем із захистом з метою аналізу та поліпшення їх властивостей. Сучасні та перспективні системи мають бути максимально захищені, проте безпека і ефективність виробництва та життєдіяльності є суперечливими критеріями. Динамічні системи із захистом від шкідливих природних чи техногенних факторів включають велику кількість процесів з різними характерними часом, причому ієрархія цих часів така, що вони розрізняються на багато порядків. Системи подібного типу моделюються сингулярними системами диференціальних рівнянь зі змінними в часі зовнішніми параметрами. Вони є досить складними щоб мати розв’язок в загальному аналітичному вигляді, але внутрішні параметри досить швидко змінюються, що дуже утруднює чисельне розв’язання рівнянь. Такі системи характеризуються порівняно простою структурою і складною поведінкою. До них відносяться не тільки системи пожежогасіння, захисту хімічних і ядерних реакторів, захисту енергосистем, захисту від паводків і катастроф в житлово-комунальному господарстві, а й деякі оборонні системи. The purpose of dissertation was to increase the safety of ergatic systems with dynamic protection by assessing the best parameters for the developed mathematical models and improving the computational methods for their analysis. The research methods are based on the integrated use of system analysis for revealing of influences and dynamic properties of technical systems with protection; qualitative theory of singular differential equations to allocate stationary sets and conditions of their stability. Asymptotic methods and numerical simulation, computational methods for solving the corresponding systems of differential equations for ergatic systems with protection were also used. In the dissertation work the new scientific results are obtained, such as: – the modified mathematical model of ergatic systems with dynamic protection was developed; – the method of a singular model analysis with an boundary layer received its further development by constructing and evaluating the accuracy of asymptotic solution for ergatic systems with dynamic protection; – the computational method for the asymptotic solution of Cauchy problems with different types of singularities and non-stationary control parameters has been improved with estimation of the small perturbation parameter for different speeds of the harmful process; – the method for analysis of protected systems` stability received its further development; – the presence of unconstrained chaotic motions in a non-autonomous system near the periodic motion of a corresponding autonomous ergatic system with protection at convergence of their oscillation periods was revealed with the help of numerical experiment. The practical value of the results obtained is that the developed methods allow us to assess the state and parameters of technical systems with protection, that leads to a steady and rapid suppression of the local harmful factors at an affordable price. The presented methods are also used in educational process of Kharkiv National University of Radioelectronics.The purpose of dissertation was to increase the safety of ergatic systems with dynamic protection by assessing the best parameters for the developed mathematical models and improving the computational methods for their analysis. The research methods are based on the integrated use of system analysis for revealing of influences and dynamic properties of technical systems with protection; qualitative theory of singular differential equations to allocate stationary sets and conditions of their stability. Asymptotic methods and numerical simulation, computational methods for solving the corresponding systems of differential equations for ergatic systems with protection were also used. In the dissertation work the new scientific results are obtained, such as: – the modified mathematical model of ergatic systems with dynamic protection was developed; – the method of a singular model analysis with an boundary layer received its further development by constructing and evaluating the accuracy of asymptotic solution for ergatic systems with dynamic protection; – the computational method for the asymptotic solution of Cauchy problems with different types of singularities and non-stationary control parameters has been improved with estimation of the small perturbation parameter for different speeds of the harmful process; – the method for analysis of protected systems` stability received its further development; – the presence of unconstrained chaotic motions in a non-autonomous system near the periodic motion of a corresponding autonomous ergatic system with protection at convergence of their oscillation periods was revealed with the help of numerical experiment. The practical value of the results obtained is that the developed methods allow us to assess the state and parameters of technical systems with protection, that leads to a steady and rapid suppression of the local harmful factors at an affordable price. The presented methods are also used in educational process of Kharkiv National University of Radioelectronics.
Keywords: ергатичні системи; шкідливі чинники; негативний зворотній зв’язок; проблеми стійкості; атрактор; збурення; сингулярність; ergatic systems; protection of harmful factors; negative feedback; stability problems; attractor; perturbation; singularity